Comments on Annalisa Coliva, Extended Rationality: A Hinge Epistemology - Baghramian, Maria (International journal for the study of skepticism, 2017)
In Extended Rationality: A Hinge Epistemology, Annalisa Coliva aims to by-pass traditional sceptical challenges to the possibility of knowledge by arguing that all thinking and knowing ultimately rely on hinge assumptions which are immune from doubt because of their foundational role in the very framework that makes knowledge and rational thought possible. In defending her position Coliva also rejects the relativist challenge that there could be incompatible but equally plausible systems of justification relying on alternative hinges or assumptions. In this response to Coliva, I argue that even if we accept that we need to rely on some core assumptions in order to get the process of rational thought going, the question of the uniqueness of these assumptions remains open. I maintain that Coliva’s two argumentative strategies against the possibility of relativism, one based on empirical considerations and a second relying on considerations from logic do not guarantee the uniqueness of hinge assumptions and the possibility of at least a moderate form of relativism looms large.